Sombor index of thorny graphs - Gutman, Ivan (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: The thorny graph of a graph G is obtained by attaching pendent vertices to the vertices of G. A mathematical study of the Sombor index of thorny graphs is undertaken. Methods: Combinatorial graph theory is applied. Results: A general expression for the Sombor index of thorny graphs is obtained, as well as lower and upper bounds. Several special cases of this general expression are pointed out. Conclusion: The paper contributes to the theory of the Sombor index.